2013
DOI: 10.3233/jad-122074
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Alzheimer's Disease Among Mexican Americans

Abstract: Background Mexican Americans are the fastest aging segment of the U.S. population yet little scientific literature exists regarding the Alzheimer disease (AD) among this segment of the population. The extant literature suggests that biomarkers of AD will vary according to race/ethnicity though no prior work has explicitly studied this possibility. The aim of this study was to create a serum-based biomarker profile of AD among Mexican American. Methods Data were analyzed from 363 Mexican American participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 66 publications
3
76
0
Order By: Relevance
“…The study results highlight the association between ethnicity, metabolic status, and disease risk, consistent with previous studies (Mayeda et al, 2013, O’Bryant et al, 2013, Zeki et al, 2012). Although the phenotypes were driven solely by metabolic values and derived independently of race, there was a significant difference in the clusters’ racial composition.…”
Section: Discussionsupporting
confidence: 92%
“…The study results highlight the association between ethnicity, metabolic status, and disease risk, consistent with previous studies (Mayeda et al, 2013, O’Bryant et al, 2013, Zeki et al, 2012). Although the phenotypes were driven solely by metabolic values and derived independently of race, there was a significant difference in the clusters’ racial composition.…”
Section: Discussionsupporting
confidence: 92%
“…Given our prior pre-clinical studies that reported a major influence of OS on testosterone’s neuroprotective/neurotoxic effects, such that under conditions of elevated OS, testosterone exerted deleterious effects [23, 24], we examined whether a correlation existed between levels of testosterone and cognitive function in aged men, and whether the relationship differed as a function of their OS status (as defined by their levels of serum homocysteine). Further, given emerging evidence on ethnic differences in the neurobiology of neurodegenerative disorders 26,27 , we also determined if the relationship between testosterone and cognitive function differed between Caucasians and Mexican-Americans. The current study is the first to investigate the impact of testosterone and ethnicity on these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our recent studies show increased cognitive dysfunction in Mexican-Americans diagnosed with AD and MCI compared to Caucasians [25, 26]. Further, studies from other laboratories have found differences in the incidence of PD between Caucasians and Hispanics [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of genome-wide association studies confirmed that expression of the ApoE e4 allele, the strongest genetic risk factor for sporadic AD, was associated with AD in whites and nonwhite ethnic groups, whereas various other genotypes were associated with AD only in whites [22]. Likewise, in the only study explicitly examining a blood-based biomarker profile of AD conducted specifically among a Latino population to date, our group found that the blood-based biomarker profile approach is highly accurate in detecting AD among US Mexican Americans and the profile was significantly different than that observed among non-Hispanic whites [23]. Additional work is needed in this area.…”
mentioning
confidence: 62%